Assistance in repackaging and digital marketing for shrimp floss businesses to expand market reach - Sayyidah Ilman Nisa; Nur Anita; Fitria Kurniasih; Fanny Nugraheni; Windy Puspitasari; Karmila Aliani Ranti; Ali Akbar; Al Ahfaz Reza Ramdani; Abdul Kamal; Fatmawati Fatmawati; Randi Syafutra (Community Empowerment, 2023)
The aim of this community service is to enhance the marketing quality of shrimp floss through repackaging and the utilization of e-commerce. This program employs a persuasive approach with partners involved in shredded meat production, assisting in the transformation of shrimp into shrimp floss. The outcomes of this initiative include new packaging designs and the digitalization of shrimp floss marketing through e-commerce, along with the dissemination of links on social media. The 2023 Rambat Village KKN MAs activities are expected to bolster the implementation of digital villages by integrating technology to support the economy in Rambat Village.